In the Land of Freedom?: Early Life of Free African Americans in the Rural Wisconsin Settlement of Pleasant Ridge, 1848-1865 - Tierney, Rachel (My University, 2016)
This research examines the free African American community of Pleasant Ridge in Grant County, Wisconsin from its founding in 1848 to the end of the Civil War in 1865. Through the experiences of the first few families to reside in his area, this study aims to illustrate the ways in which slavery continued to affect lives in the North at this time. These people demonstrate not only that some saw the North as a “land of freedom,” but also that this ideal was not the reality. By describing Pleasant Ridge residents’ limited freedom, one can see that the implications of slavery were not contained by the borders of the South. In fact, slavery and its consequences were impacting lives well beyond its legal constraints. Thus, this work sheds light on both the myth and the reality of the North through the lives of those in Pleasant Ridge.
Keywords: Slavery -- Wisconsin; Pleasant Ridge (Wis.); Grant County (Wis.)